2019
DOI: 10.3390/nu11061304
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Percent Body Fat on All-Cause Mortality among Adequate Dialysis Patients with and without Insulin Resistance: A Multi-Center Prospective Cohort Study

Abstract: The association between body fat and mortality in hemodialysis patients remains controversial. We examined the effect of percent body fat (PBF) on all-cause mortality among adequate hemodialysis patients with and without insulin resistance (IR). A prospective cohort study was conducted on 365 adequate hemodialysis patients (equilibrated Kt/V ≥ 1.2) from seven hospitals. Patients’ characteristics and clinical and biochemical parameters were assessed at baseline between September 2013 and April 2017. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Marcelli et al investigated an international European cohort of 37,345 hemodialysis patients (age 62.7 ± 15.2 years) and found that low fat tissue index (<10th percentile), determined with BIA, was associated with significantly increased mortality compared to the reference fat tissue index between the 10th and 90th percentile (HR 1.19; 95% CI 1.08-1.31; p < 0.001) [78]. Moreover, Caetano et al [79] and Duong et al [80] reported that low fat mass determined using BIA was significantly associated with higher risk of mortality in hemodialysis patients. Based on these results, it is suggested that greater fat mass is associated with better survival in hemodialysis patients in contrast to the general population.…”
Section: Fat Mass and Mortalitymentioning
confidence: 97%
“…Marcelli et al investigated an international European cohort of 37,345 hemodialysis patients (age 62.7 ± 15.2 years) and found that low fat tissue index (<10th percentile), determined with BIA, was associated with significantly increased mortality compared to the reference fat tissue index between the 10th and 90th percentile (HR 1.19; 95% CI 1.08-1.31; p < 0.001) [78]. Moreover, Caetano et al [79] and Duong et al [80] reported that low fat mass determined using BIA was significantly associated with higher risk of mortality in hemodialysis patients. Based on these results, it is suggested that greater fat mass is associated with better survival in hemodialysis patients in contrast to the general population.…”
Section: Fat Mass and Mortalitymentioning
confidence: 97%
“…In our sample, men, NDD, and KTx patients had higher prevalence of obesity and lower prevalence of low muscle mass and sarcopenia. In addition, adiposity was a protective factor for low muscle mass diagnosis, as in the obesity paradox in CKD, which is not well understood [ 6 , 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, sarcopenia was associated with increased mortality regardless of estimated glomerular filtration rate, but excess adiposity modified this association only among persons with CKD [ 6 ]. Also, insulin derangements were shown to modify the relationship between adiposity and mortality, as body fat showed a protective effect on survival only in HD patients with insulin resistance [ 12 ]. The studies evidence that interfering factors could play a role in the obesity paradox, but it is yet unclear whether increased muscle mass or increased body fat confers the survival advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to muscle depletion, obesity is also common among CKD patients [10,11]. Obesity has a controversial role in survival rates and clinical prognosis in CKD patients [6,9,12]. Currently, body mass index (BMI) is the most widely used obesity measure, but the index is an imperfect measure of adiposity [10].…”
Section: Introductionmentioning
confidence: 99%